Solving the jigsaw of conflict-related environmental damage: Utilizing open-source analysis to improve research into environmental health risks. (18th November 2019) - Zwijnenburg, Wim; Hochhauser, David; Dewachi, Omar; Sullivan, Richard; Nguyen, Vinh-Kim
Abstract: Investigation of the environmental impacts of armed conflict has been made easier in recent years with the development of new and improved methods for documenting and monitoring environmental damage and pollution. For decades, research into conflict-linked environmental damage and its links to human health have been overlooked and research underfunded, hindering a complete humanitarian response and effective post-conflict reconstruction. Recent developments in the field of open-source investigation have shown promising results due to the increased use of mobile phones, access to the internet and freely available methods for remote observation by satellite. Utilizing and analysing these sources of data can help us to understand how conflicts are associated with environmental damage, pollution and their negative impacts upon public health. Further research and development in this field will help to inform more effective humanitarian responses, mitigate risks to health and identify priorities for post-conflict reconstruction programs. Data-driven open-source research can also strengthen international discussions on state accountability for military activities and build a case for the responsibility of warring parties to protect the environment as well as the people who depend on it.